Multilayer piezoelectric energy scavenger for large current generation - Song, Hyun-Cheol; Kim, Hyung-Chan; Kang, Chong-Yun; Kim, Hyun-Jai; Yoon, Seok-Jin; Jeong, Dae-Yong (SPRINGER, 2009)
Piezoelectric energy harvesting system is promising to the energy source of wireless sensor nodes for ubiquitous sensor networks. The piezoelectric material has been usually considered as a high voltage and low current source. When charging current into the thin film battery or supercapacitor, a larger current is needed to shorten the charging time. In order to increase the current in the piezoelectric energy harvesting, multilayer ceramics were fabricated. N-layer multilayer ceramics decreased the voltage but increased the current N times. The impedance of the multilayer ceramics are matched to 1 k Omega which is similar to the impedance of general electrical devices. The multilayer piezoelectric generator could be directly employed for electrical device without the additional electrical circuit to improve efficiency.